2010
DOI: 10.1029/2010jb007820
|View full text |Cite
|
Sign up to set email alerts
|

Brittleness of fracture in flowing magma

Abstract: [1] Understanding the transition to brittle fracture of flowing magma is essential for estimating the explosiveness of a volcanic eruption. In order to quantify brittleness of flowing magma, a new parameter b is introduced, which is a function of the ratio of the rate of change of the strain energy due to elastic distortional deformation to the mechanical power due to total distortional deformation rate. From the perspective of b, dependence of brittle fracture of magma on stress, decompression rate, strain ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 52 publications
2
12
0
Order By: Relevance
“…The rates and manifestations of deformation are indicative of the underlying processes, e.g., at Super-Sauze aseismic viscous creep likely occurs in areas of lower displacement rates and brittle failure manifests as slidequakes where rates are higher. This dependence of deformation mode on loading rate may be similar to that inferred for ascending magma, in which fast-rising magma deformed brittle and generated earthquakes, while slow-rising magma is characterized by ductile, aseismic deformations (e.g., Tuffen et al, 2003;Ichihara and Rubin, 2010). The observations at Super-Sauze support this hypothesis of a relationship between loading rate and slidequake generation.…”
Section: Discussionsupporting
confidence: 73%
“…The rates and manifestations of deformation are indicative of the underlying processes, e.g., at Super-Sauze aseismic viscous creep likely occurs in areas of lower displacement rates and brittle failure manifests as slidequakes where rates are higher. This dependence of deformation mode on loading rate may be similar to that inferred for ascending magma, in which fast-rising magma deformed brittle and generated earthquakes, while slow-rising magma is characterized by ductile, aseismic deformations (e.g., Tuffen et al, 2003;Ichihara and Rubin, 2010). The observations at Super-Sauze support this hypothesis of a relationship between loading rate and slidequake generation.…”
Section: Discussionsupporting
confidence: 73%
“…The shear-induced brittle fracturing at conduit margins described here is thought to be responsible for the earthquakes that often accompany extrusion of highly viscous magma plugs, which many authors have observed both texturally and seismically, and which can be an effective precursor for dome eruptions [Stasiuk et al, 1996;Tuffen et al, 2003;Tuffen and Dingwell, 2005;Iverson et al, 2006;Cashman et al, 2008;Lavallee et al, 2008;Tuffen et al, 2008;Pallister et al, 2012]. Furthermore, this behavior facilitates mobilization of silicic magmas that are naturally resistant to flow.…”
Section: Explosive-effusive Transitionmentioning
confidence: 74%
“…Crystal rearrangement during shear, clearly observed in our experiments, has been shown to induce the localization of deformation necessary for brittle failure of silicate melts [ Ichihara and Rubin , ; Laumonier et al , ]. Okumura et al [] also demonstrated strain localization occurring in crystal‐free vesicular rhyolite, similar to sample b36×0Ω2.…”
Section: Discussionmentioning
confidence: 99%
“…the stress‐strain rate relationship becomes non‐linear). Silicate melts can thus transition from fluid to solid‐like response [ Ichihara and Rubin , 2010], and undergo brittle fracture depending on the state of stress, strain rate, and temperature conditions. Maxwell's theory of viscoelastic deformation provides a theoretical framework for the study of magma fracture in silicic magma.…”
Section: Magma Fracturementioning
confidence: 99%